Perencanaan Pendidikan Di Mas Al-Washliyah 22 Tembung: Strategi Peningkatan Mutu Pendidikan Berbasis Visi Dan Misi Madrasah - Faisal Fahmi Rambe; Ikhwan El-Musthofa; Inom Nasution (Journal on Education, 2024)
This study examines educational planning at Madrasah Aliyah Swasta (MAS) Al-Washliyah 22 Tembung as a strategy for improving educational quality. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation study. The results show that educational planning at MAS Al-Washliyah 22 Tembung focuses on four main aspects: integrated curriculum development, teacher competency improvement, infrastructure provision, and student character strengthening. This planning is based on the madrasah's vision and mission as well as SWOT analysis. Curriculum development aims to integrate general knowledge with Islamic values. Teacher competency improvement programs are conducted through training and further studies. Infrastructure provision includes the procurement of laboratories, libraries, and information technology. Student character strengthening is planned through extracurricular activities and religious programs. This study concludes that educational planning at MAS Al-Washliyah 22 Tembung represents a comprehensive effort to improve educational quality and realize the madrasah's vision and mission.